2021
DOI: 10.1161/circoutcomes.120.007191
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Coronary Artery Abnormalities and Resistance to Intravenous Immunoglobulin Plus Corticosteroid Therapy in Severe Kawasaki Disease

Abstract: Background: Coronary artery abnormalities (CAAs) still occur in patients with Kawasaki disease receiving intensified treatment with corticosteroids. We aimed to determine the risk factors of CAA development and resistance to intensified treatment in Post RAISE (Prospective Observational Study on Stratified Treatment With Immunoglobulin Plus Steroid Efficacy for Kawasaki Disease)—the largest prospective cohort of Kawasaki disease patients to date. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
4
19
2
Order By: Relevance
“…Our study observed that the baseline Z score of the left main coronary artery before the primary treatment was a heightened risk factor for CAA development, and the same result was observed in the high-risk patients with KD as defined by a Kobayashi score ≥4 points (see Supplementary File 2 ). However, inconsistent with the results of a multicenter and prospective observational study that was conducted in Japan, our study showed no relationships between age <1 year or IVIG resistance and CAA development ( 23 ), which was probably because of the small sample size of high-risk patients with KD. Our study may have been underpowered to conduct a highly informative multivariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study observed that the baseline Z score of the left main coronary artery before the primary treatment was a heightened risk factor for CAA development, and the same result was observed in the high-risk patients with KD as defined by a Kobayashi score ≥4 points (see Supplementary File 2 ). However, inconsistent with the results of a multicenter and prospective observational study that was conducted in Japan, our study showed no relationships between age <1 year or IVIG resistance and CAA development ( 23 ), which was probably because of the small sample size of high-risk patients with KD. Our study may have been underpowered to conduct a highly informative multivariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…To determine the relative effect of each risk factor for IVIG resistance in high-risk KD, we performed a logistic regression analysis, which revealed that high-risk KD with IVIG resistance was significantly associated with six baseline laboratory variables (WBC, serum levels of ALT, AST, TSB, and sodium, and B/A ratio) and two clinical characteristics (days of illness at primary treatment and the Xie Liping risk score). These variables plus the CRP level, PLT count, and age <1 year, all of which were previously reported as risk factors for IVIG resistance ( 3 , 7 , 16 , 22 , 23 ), but not the Xie Liping risk score or TSB level, were included in the logistic regression analysis ( Table 2 ). The B/A ratio, calculated as the TSB level divided by the ALB level, was included in the multivariable analysis instead of the two separate indicators; the Xie Liping risk score was also excluded from the multivariable analysis because the variables included in this risk score, such as days of illness at primary treatment, the serum sodium level, age, the WBC count instead of the percentage of neutrophils, and B/A ratio instead of the ALB level, were included in the multivariable model.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that age <1 year and >5 years and males are risk factors for cardiovascular complications in patients with KD, which is partially consistent with our findings. 3,[13][14][15][16][17] This study found that patients aged >5 years had the highest IVIG unresponsiveness incidence, but not CAA incidence. This result, however, was not statistically significant, probably because of the low number of patients in this group.…”
Section: Discussionmentioning
confidence: 55%
“…Third, several known predictive factors such as neutrophil-to-lymphocyte and platelet-lymphocyte ratios [34] were not evaluated. Forth, insu cient reduction in the serum CRP level was additionally included in the de nition of IVIG resistance in the present study, while only persistent fever was evaluated in many studies [35,36].…”
Section: Discussionmentioning
confidence: 99%